University TV and extension: A possible dialog - Fregona Rocha, Camila (Guará Journal, 2018)
This article has as its theme the relationship between University TV and University Extension. The objective is to present the discussion about the role of University TVs, reflecting on the potential of these vehicles for an extensionist activity and on how they could understand the university extension in its design and programming. For this, a bibliographical survey is used to reflect on the concept of University TV, added to the foundation provided in the current legislation on the subject. In addition to the theoretical discussions, we present an account of the extension actions adopted by TV UFES, which shows that integration between University TV and University Extension is possible. The results presented by the extension project addressed in this study indicate that this relationship is not only possible but must be constant and extended.